Promoting the hydrogen evolution reaction through oxygen vacancies and phase transformation engineering on layered double hydroxide nanosheets - Liu, Shujie; Zhu, Jie; Sun, Mao; Ma, Zhixue; Hu, Kan; Nakajima, Tomohiko; Liu, Xianhu; Schmuki, Patrik; Wang, Lei (Journal of Materials Chemistry A, 2020)
In electrocatalysis, layered double hydroxide (LDH) materials have attracted considerable interest in promoting the oxygen evolution reaction (OER). For the hydrogen evolution reaction (HER), these materials show a poor electrocatalytic activity. In this work, we take CoFe LDH grown on nickel foam as a model system, and for the first time we treat CoFe LDH under plasma etching conditions, which results in a highly active HER electrocatalyst in alkaline media. Massive defects and amorphous phase formation occur during plasma etching. More importantly, phase transformation of CoFe LDH into CoFe2O4 takes place. Additional introduction of Ce leads to more active sites and improved electrical conductivity, which provide an overpotential of 73 mV at a current density of 10 mA cm-2 for V-Ce/CoFe LDH. The experimental results match well with DFT calculations, proving that defect engineering, phase transformation, and electronic structure tailoring can result in a high efficiency of HER activity. Moreover, a cell constructed of CoFe LDH‖V-Ce/CoFe LDH is capable of overall water splitting with a cell voltage as low as 1.65 V at 10 mA cm-2 and a remarkable long-term stability of 60 h. The plasma etching strategy can also be effective for other LDH-based electrocatalysts (e.g. NiFe LDH and NiCo LDH), which demonstrates the universality of the strategy for improving HER performance. This work provides a simple but feasible pathway for designing alkaline HER electrocatalysts based on advanced LDH materials.
CRIS-Team Scopus Importer:2020-02-18